PENGARUH PRICE, PROMOTION, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS APLIKASI KONSUMEN MCDONALD'S DI JAKARTA) - Terren Haekal Wiramawan, (2023)
This research is a quantitative study that aims to analyze the effect of price, promotion, and brand image on purchasing decisions in the McDonald's application. The population in this study were McDonald's application users in Jakarta with the sampling used was non probability sampling with purposive sampling technique which obtained a sample of 100 respondents by distributing questionnaires. Data processing tools to help analyze the data in this study using Smart PLS version 4.0.9.3. The results of this study are that price has a positive and significant effect on purchasing decisions with an original sample value of 0.349, promotion has a positive and significant effect with an original sample value of 0.215, and brand image has a positive and significant effect on purchasing decisions with an original sample value of 0.398 while the contribution of the price, promotion, and brand image variables together is indicated by the adjusted Rsquared value of 74.50% to the purchasing decision. While the remaining 25.50% is caused by other factors outside this research model.